Reconstruction of the Coracoclavicular Ligament Complex Utilizing an All-Suture Tape Cerclage Technique - William A. Ranson, M.D.; Laura Thurber, M.D.; Akshar V. Patel, B.S.; Christoph Schroen, B.S.; Carl M. Cirino, M.D.; Patrick J. Denard, M.D.; Paul J. Cagle, M.D. (Arthroscopy Techniques)
Current techniques for the operative management of acromioclavicular joint separation injuries are plagued by a high rate of postoperative complications. Loss of fixation has been the most difficult challenge to overcome, with a recent meta-analysis finding postoperative subluxation in over 20% of cases. No gold-standard surgical treatment has been established despite over 100 unique procedures having been described in the literature. All-suture fixation techniques have shown promise but were previously limited by issues inherent to the properties of the available suture materials. Recently, however, a modern suture product with unique properties has been made commercially available. The senior authors sought to adapt this material to fixation of injuries of the coracoclavicular ligament complex. In this Technical Note, we present an all-suture tape cerclage technique for the fixation of high-grade acromioclavicular separation injuries (Rockwood types IV, V, and VI). By controlling the ultimate knot stack position through the directionality of suture passage, this technique negates the risk of subsequent hardware irritation. Further, by avoiding the formation of coracoid tunnels, the risk of iatrogenic coracoid fracture is minimized. Importantly, this technique is simple and reproducible while also minimizing material requirements and cost.